Holistic qur’anic pedagogy: an alternative paradigm for islamic education amid global crises - Mahrus; Ahmad Munadirin; Achmad yusuf; Camila Fatah Suroyya; Mohamad Ardin Suwandi (At Turots: Jurnal Pendidikan Islam, 2025)
This research seeks to realign Islamic education with transcendental values in the midst of the rapid flow of globalization, digitalization, and the deepening moral crisis of the younger generation. This study offers a holistic framework of Qur’anic pedagogy by integrating the epistemological, methodological, and ethical dimensions excavated from Surah al-’Alaq and Surah Luqman. Using a qualitative research design based on literature study and content analysis, Qur’anic verses are examined through linguistic and contextual studies, then associated with contemporary educational challenges. The analysis of Surah al-’Alaq emphasizes the importance of transcendental literacy as the foundation of epistemology, the role of habituation and repetition as a means of internalizing values, and the adaptation of learning media in response to technological developments. Meanwhile, Surah Luqman provides an ethical and dialogical framework that emphasizes monotheism, gratitude, persuasive communication, and overall character building. The integration of these two surahs gave birth to a Qur’anic pedagogical model that combines cognitive, moral, spiritual, and social dimensions, so that education is able to develop intellectual capacity while fostering ethical and spiritual awareness. Practically, this framework is the basis for designing a curriculum based on unity of knowledge, dialogical and experiential learning strategies, and the ethical use of digital technology to strengthen students’ critical literacy, media skills, and moral resilience. By placing Qur’anic pedagogy in the discourse of education in the 21st century, this research contributes theoretically by expanding the study of Islamic pedagogy from normative descriptions to methodological frameworks, as well as practically offering a model that can be adopted by Islamic educational institutions to produce intelligent, moral, and transcendental consciousness generations.